The laboratory in the multidisciplinary diagnosis of differences or disorders of sex development (DSD) - Granada Maria Luisa; Audí Laura (Advances in Laboratory Medicine, 2021)
46,XY differences/disorders of sex development (DSD) involve an abnormal gonadal and/or genital (external and/or internal) development caused by lack or incomplete intrauterine virilization, with or without the presence of Müllerian ducts remnants.